Molecular detection of Human Papillomavirus genotype-16&-18 in tissues from patients with prostate cancer and benign prostatic hyperplasia - AL-Mahbobi, Taghreed F.; Mohammed Ali, Saad H.; AL- Kurtas, Mohammed A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: High oncogenic-risk genotypes of human Papillomavirus (HPV) infect a wide range of human cells, including prostate tissue that give rise to benign prostatic hyperplasia and prostatic adenocarcinomas.Objectives: This study aimed to detect DNA of HPV genotype-16 &18 using in situ hybridization technique in prostatic tissues from benign prostatic hyperplasia and prostatic adenocarcinomas, and elucidate the association between these HPV genotypes and prostatic carcinogenesis.Patients and methods: Forty-eight (48) formalin-fixed, paraffin embedded prostatic tissue blocks were obtained ,among them (28) tissue biopsies from prostatic carcinoma with different grades and (20) benign prostate hyperplastic tissue blocks as well as (10) apparently normal prostate tissue autopsies which were collected from the archives of Forensic Medicine Institute / Baghdad and used as prostate healthy control groups. Detection and genotyping of HPV was done by highly sensitive in situhybridization technique.Results: The signals of in situ hybridization reactions of both HPV-16 and HPV-18 in prostate cancer cases in the present study was 25% (7 / 28) whereas in BPH, HPV-16 was detected in 45 %( 9 /20) and HPV-18 was presented in 35 %( 7/ 20). Neither HPV-16 nor HPV-18 was detected in the apparently healthy control group.The percentages of HPV 16 and HPV18 were increasing with advancing of grade of prostate cancer.Conclusion: Our results indicate that the oncogenic HPV-16 might contribute to the development of subset of prostate tumors. In addition, HPV16&18 might have a crucial role in progression of the prostate cancer and benign prostatic hyperplasia